Discursos envolventes no ensino da língua portuguesa escrita para surdos em uma escola comum: análise linguístico-discursiva - Espírito Santo, Joseane dos Santos do (2019)
The present research reflected on the discourses’ implications that were naturalized in Portuguese teaching practices for deaf students in the common school, from the perspective of Inclusive Education (SALAMANCA, 1994; MANTOAN, 2006; BRAZIL, 2015). We understand that language practices in their different modalities need a reflection on them, based on the research of linguistic-discursive practices offered to these students. Anchored in Applied Linguistics (MOITA LOPES, 2006), this research departs from the discourses (BAKHTIN, 2003, 2006, SOUTO MAOR, 2009) presents in language teaching and learning practices as well as the possible implications on language teaching for the Deaf students. The methodological approach of the study is qualitative (LÜDKE; ANDRÉ, 1986), ethnographic in nature (MOUREIRA, 2011), with actions carried out within the case study mode (GIL, 2007, 2008). The research was conducted in the city of Maceió - AL, in a school of the state basic education, with a listener teacher, who teaches the Portuguese Language discipline in a mixed class with deaf and hearing students in 2017. For development We used the following data collection procedures: bibliographic research, documentary research, questionnaire and interview application. This research is necessary to understand the engaging discourses present in the process of teaching a second language, which redefine the binary idea of normality and cause implications on the process and practices of teaching and learning of deaf students.